A ictiofauna no monitoramento da qualidade ambiental em um distrito industrial do estuário amazônico - VIANA, Andréa Pontes (Universidade Federal do Pará, 2013)
The district of Vila do Conde, in the municipality of Barcarena, is a prominent industrial hub, constituting a risk factor for water quality. Given this, the present study focused on the environmental quality of the aquatic habitats adjacent to this site, using the fish community as a bioindicator and liver two species of fish as a biomarker histopathological. The collection of abiotic data (water samples) and fish specimens was organized in three distinct zones, representing different levels of impact. Zone 1 was located in the vicinity of the Vila do Conde cargo terminal, where the risk of contamination was highest. Zone 2 was in the Capim Island, located on the border between the municipalities of Bacarena and Abaetetuba, classified as a median risk area due to its relative proximity to the port. Zone 3 was in Onças Island, which was classified as minimum risk, due to its distance from the industrial district of Vila do Conde. Two different types of environment – the main river channel and marginal tidal creek were sampled in all three zones. Samples were collected every two months, covering the region’s principal climatic periods - rainy-dry transition (June 2009), dry season (September 2009), dry-rainy transition (January 2010), rainy season (April 2010), in one year collection. Data was collected using monofilament gillnets and block net. Aiming to evaluate the water quality considering different tools, this study was divided into three parts. In the the first part, the icthyofauna was used as an bioindicator of water quality (Chapter 1). In the second part, two species abundant with different feeding habits, Plagioscion squamosissimus and Lithodoras dorsalis, to assess the health of the environment through the use of liver as a biomarker histopathological (Chapter 2). Finally, all families of descriptors (chapters 1 and 2), were combined into biological integrity indexes in chapter 3. The analysis of the icthyofauna as an bioindicator showed differences in the composition between zones and environments (main channel and tidal creek), for the different groups of descriptors. Considering the 77 species captured, only 23 species were recorded in comparison with the less impacted areas. Also, large fish were least common in zone 1. In the present study, the smaller proportion of larger-sized fish recorded in the impacted areas may reflect an ecological response to anthropogenic disturbance. Biomarker analysis, carried out through the liver histopatologic study, was efficient to detect the influence of antropogenic factors in the heatlh of P. squamosissimus e L. dorsalis. The MAV (Mean Assessment Values), HAI (Histological Alteration Index) e o MDS (multidimensional scaling) analysis all indicated clear differences between the areas surveyed. The alterations were more severe (in some cases, irreversible) in zone 1, which was closest to the port and the industrial district. The principal alterations observed in the tissue of both species included an increase in the number of melanomacrophagous centers, fatty degeneration, inflammation, congestion, hepatitis, and focal necrosis. The hepatic alterations observed in the present study were generally more intense in the carnivorous P. squamosissimus, which feeds mainly on shrimp in the region of the study area. Though integrity indexes, all community information were combined into metrics. In the present study, considering the ABC curve, in the main channel and creek, the zones 1 and 2 were classified as moderately disturbed, which predicts an increase in the relative abundance of opportunistic species. The BHI (Estuarine biological health index), EFCI (Estuarine fish community índex), TFCI (Transitional fish classification índex) e EBI (Estuarine biotic integrity index) were considered to be excellent indicators of the ecological integrity of the different sectors of the study area, and were especially effective for the demonstration of the critical alterations of the fish community of zone 1. It was also possible to identify alterations to the environment of zone 2. The procedures adopted in the present study were nevertheless adequate for the detection of the alterations to the environment which have occurred in the vicinity of the town’s industrial district and cargo terminal and are able to be replicted in others estuarine areas. However, more reliable information on the bio-accumulation of heavy metals in these species will be necessary. This is especially important due to the prominence of both species in the diet of the local communities.